2000
DOI: 10.1021/jp000059s
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Photoinduced Isomerization and Back-Isomerization of the Cyanine Dye Cy5 by Fluorescence Correlation Spectroscopy

Abstract: Cy5 is one of a few commercially available dyes in the near-infrared wavelength range. In this study, the fluorescence fluctuations of Cy5 have been investigated under steady-state excitation conditions by fluorescence correlation spectroscopy (FCS). The fluctuations in fluorescence are compatible with and can be used to characterize the photoinduced isomerization and back-isomerization, as well as the transitions between the singlet and triplet states of the dye. By employing a simple kinetic model, the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
477
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 360 publications
(520 citation statements)
references
References 80 publications
42
477
1
Order By: Relevance
“…When attached to a lipid membrane, MC540 is likely to display slower isomerization rates, due to the presumably larger viscous drag experienced. This is well in line with previous FCS solution studies, where for the dye Cy5 was found to increase in proportion to the viscosity of the solution 21 . In the FCS curves recorded from the liposome samples one extra exponential relaxation process in the time range of 100 ns could be noticed, reasonably well in agreement with the theoretically expected rotational correlation times ( = 100 ns, from the Debye expression) of the vesicles used (100 nm diameter).…”
Section: Results and Discussion Isomerization Kinetics Of Mc540 In Etsupporting
confidence: 93%
See 1 more Smart Citation
“…When attached to a lipid membrane, MC540 is likely to display slower isomerization rates, due to the presumably larger viscous drag experienced. This is well in line with previous FCS solution studies, where for the dye Cy5 was found to increase in proportion to the viscosity of the solution 21 . In the FCS curves recorded from the liposome samples one extra exponential relaxation process in the time range of 100 ns could be noticed, reasonably well in agreement with the theoretically expected rotational correlation times ( = 100 ns, from the Debye expression) of the vesicles used (100 nm diameter).…”
Section: Results and Discussion Isomerization Kinetics Of Mc540 In Etsupporting
confidence: 93%
“…These findings are well in line with the excitation irradiance dependence of the isomerization parameters and , as recorded by FCS in this work ( Figures 1C,D) and in previous studies. 21,22 Taken together, this allowed us to associate the dark state observed in the TRAST measurements with the isomerization of MC540. The recorded TRAST were found to be well described by a single exponential term according to Equation 10 and 11, indicating the presence of only a single dark state.…”
Section: Isomerization Measurements In Live Cells With Trastmentioning
confidence: 83%
“…t2 is much slower than the relaxation time of Cy5 in the presence of oxygen, which was measured to be on the order of Ϸ1 s (20). However, the triplet-state lifetime of Cy5 might be dramatically lengthened in the absence of oxygen, a very effective triplet-state quencher.…”
Section: Resultsmentioning
confidence: 96%
“…2A). These relaxations may be tentatively identified as a combination of a trans-cis isomerization and triplet-state relaxation (20). To mimic a situation of direct excitation of Cy5, S15 protein (3-h off rate) was attached to the junction so that the molecule is in the folded configuration, giving high FRET efficiency (17).…”
Section: Resultsmentioning
confidence: 99%
“…This changes the fluorescence emission per molecule, and the fluorescence brightness coefficient Q of the studied molecules. This strategy, has been exploited to monitor inter-or intra-molecular dynamics, influenced by fluorescence quenching (Bonnet et al, 1998), (Chattopadhyay et al, 2002), a range of photophysical processes inherent to the fluorophore marker molecules, including triplet state formation (Widengren et al, 1995), photo-isomerisation (Widengren and Schwille, 2000), and photo-induced charge transfer (Widengren et al, 2007), but also other processes influencing fluorescence blinking, such as ion exchange involving ion-sensitive fluorophores, as discussed in this review.…”
mentioning
confidence: 99%